Sodium arsenite induces apoptosis and Epstein–Barr virus reactivation in lymphoblastoid cells - Zebboudj, Abderezak; Maroui, Mohamed Ali; Dutrieux, Jacques; Touil-Boukoffa, Chafia; Bourouba, Mehdi; Chelbi-Alix, Mounira K.; Nisole, Sébastien (Biochimie, 2014)
Epstein–Barr virus (EBV) is associated with several malignancies, including carcinomas, such as nasopharyngeal carcinoma, and lymphomas, such as Burkitt's lymphoma and Hodgkin's lymphoma. The Latent Membrane Protein 1 (LMP1) is the major oncogene protein of EBV as its expression is responsible for the induction of cell transformation, immortalization and proliferation. Arsenic trioxide was shown to induce a cytotoxic effect on nasopharyngeal cancer cells associated with LMP1 down-regulation. However, the effect of arsenic on EBV-associated lymphoproliferative malignancies has been less studied. We investigated the effect of two different arsenical compounds, arsenic trioxide (As2O3) and sodium arsenite (NaAsO2) on the induction of cell death in P3HR1 cells, an Epstein–Barr virus-positive Burkitt lymphoma derived cell line. Both compounds inhibited cell growth and induced cell death. By flow-cytometry and Western blot analysis, we provide evidence that NaAsO2 induced caspase-dependent apoptosis whereas As2O3 triggered autophagic cell death. Furthermore, we show that NaAsO2 treatment led to a dramatic decrease of the expression level of LMP1 and the cellular protein PML. Importantly, this down-regulation was associated with a reactivation of EBV lytic cycle through the induction of immediate-early proteins Zta and Rta. These results are in agreement with a model in which LMP1 maintains EBV in a latent state by stabilizing PML expression. Altogether, our results suggest that NaAsO2 would represent a better therapeutic candidate than As2O3 in EBV-induced B lymphoma for its capacity to promote viral reactivation. •Arsenic trioxide induces cell death through autophagy in P3HR1 cells.•Sodium arsenite exerts its cytotoxic effect on P3HR1 cells via apoptosis.•Sodium arsenite induces a dramatic decrease of LMP1 and PML protein levels.•Sodium arsenite triggers EBV reactivation in P3HR1 cells.•PML degradation is correlated with EBV reactivation.